1997
DOI: 10.1046/j.1365-2265.1997.1400957.x
|View full text |Cite
|
Sign up to set email alerts
|

An account of the quality of life of patients after treatment for non‐functioning pituitary tumours

Abstract: We found that the quality of life of patients treated and under follow up for non-functioning pituitary tumours was similar to that of patients treated by mastoid surgery and under similar follow up. The pituitary patients deficient in two hormones and thus most likely to be GH deficient were also similar to the controls. These results suggest that adding GH replacement in this patient group may not be routinely indicated for improvement in quality of life and needs careful assessment. Patients who had receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 12 publications
12
53
3
Order By: Relevance
“…scores from the study population with the population norms for individuals aged 55-59 from the Oxford Healthy Life Survey (18) and with published results of scores for 48 patients with non-functioning pituitary tumours age 59 years (S.D. 12 years) from the Oxfordshire region (19). These groups were of comparable mean age with our study group aged 58 (S.D.…”
Section: Results Of Examinationsupporting
confidence: 60%
See 1 more Smart Citation
“…scores from the study population with the population norms for individuals aged 55-59 from the Oxford Healthy Life Survey (18) and with published results of scores for 48 patients with non-functioning pituitary tumours age 59 years (S.D. 12 years) from the Oxfordshire region (19). These groups were of comparable mean age with our study group aged 58 (S.D.…”
Section: Results Of Examinationsupporting
confidence: 60%
“…Scores were compared with normative data for a UK population (18) and with those of 48 patients with nonfunctioning pituitary tumours of mean age 59 (S.D. 12) years from the Oxfordshire region (19).…”
Section: Quality Of Life Assessmentsmentioning
confidence: 99%
“…Although most reports on QoL using generic questionnaires in NFPA describe a low QoL after treatment (7,11,41,75,76), there are also descriptions of normalization of QoL, after successful treatment, attaining scores comparable to those seen in a healthy population (77,78). As already mentioned, compared to that of other pituitary adenoma patients, QoL of NFPA patients was similar to that of patients treated for prolactinoma, and better than that of patients diagnosed with CD and acromegaly (11,39,79,80).…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 71%
“…Prior radiotherapy reportedly is followed by impaired mental health and less energy levels, without affecting the general health perception (77,78). Abnormal scores in energy, physical ability and anxiety have also been R23 Review S M Webb and others Quality of life in pituitary disease www.eje-online.org described in patients with NFPA who experience a tumour recurrence (77,81).…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 99%
“…Examples include Bulow et al (8) who found a higher prevalence of mental disorders and distress in hypopituitary women (relative risk of mental disorders 4.5, 95% confidence interval 1-21), with reduced social attachment and integration and an increased prevalence of obsessive-compulsive, phobic and psychotic symptoms. (27) used patients who had previous mastoid surgery as their control group. Overall, there was no significant difference in QOL, but those pituitary patients treated with radiotherapy had impaired mental health, more depression and decreased control of their emotions (assessed using the Short Form-36 and Psychological General Well-Being (PGWB) questionnaires).…”
Section: Discussionmentioning
confidence: 99%